Información sobre drogas: instituciones y recursos humanos en Bolivia (1993) - Carvajal A., Paola A. (Drogas - investigación para el debate, 1993)
"Basic directory lists institutions, psychologists, and other resources in Bolivia that provide drug addiction prevention and rehabilitation programs"--Handbook of Latin American Studies, v. 57